THE EFFORT TO IMPROVE MODERATION OF RELIGION IN INDONESIA (A STUDY ON THE YOUTUBE MINISTRY IN THE REPUBLIC OF INDONESIA) - Muya Syaroh Iwanda Lubis; Asrindah Nasution; Nurhayati Nurhayati; Ali Mustafa; Budiman Purba (Universitas Dharmawangsa Medan, 2022)
ABSTRACTSince the discourse on religious censorship was presented by minister lukman (2014-2019) judge saifuddin (2014-2019), the ministry of religions has continued to develop knowledge and strengthen religious censorship narratives through various platforms in the digital world. The study focuses on increased religious censorship by the ministry of the republic of Indonesia on youtube, the most popular social media platform for today's Internet users. Using a method of analysis of content with a descriptive analysis method, the study reaches several conclusions. First, in intensity, the use of the youtube channel in strengthening religious censorship issues still needs to be increased. Of the total of 318 videos uploaded to the youtube account by the ministry of religion, only 15 (4.71%) contain content on censorship and religious harmony. The annual frequency was still low, and even in 2019 there was no content on moderation and religious harmony. Second, the concept of religious censorship is still applied primarily to intellectuals who have not touched millennials. Its trend is still limited in eradicating negative issues related to the government's religious regulation program. Third, according to the warganet reaction data on censored and harmonized video content remains low. It has been found that netizens prefer the term of harmony to moderation. This suggests that the people of Indonesia in general prefer harmony, but there are still some interpretations or negative impressions of the term